OVERVIEW OF HEMOGLOBIN VALUE ON PRE AND POST RADIOTHERAPY IN PEDIATRIC CANCER PATIENTS: Study at RSUP Dr. Kariadi Semarang - Osten Owenjoy Binsar Pakpahan; Yetty Movieta Nency; RR. Lydia Purna Widyastuti Setjadiningrat Kuntjoro; Christina Hari Nawangsih Priharsanti; Edward Kurnia Setiawan L (Jurnal Kedokteran Diponegoro)
Background: Cancer is a deadly disease that gets less attention in childhood. One of the manifestations of cancer in children is anemia. As many as 50% of cancer patients will experience anemia. Radiotherapy is one of the last treatments for various types of cancer. Radiotherapy can affect hematopoiesis, thereby reducing hemoglobin production. Aim: To describe pre and post-therapy Hb levels in pediatric cancer patients undergoing radiotherapy. Methods: This research is a descriptive study with Cross-sectional design using electronic medical records of as many as seventy eight people and then collecting data in the form of age, gender, patient diagnosis, and hemoglobin levels before and after radiotherapy. Results: Pre-radiotherapy and post-radiotherapy hemoglobin levels decreased significantly between the two groups (p<0.05). Conclusion: There is a significant difference between pre-and post-radiotherapy reduced hemoglobin levels in pediatric cancer patients undergoing radiotherapy